JIRA Agile essentials : bring the power of Agile to Atlassian JIRA and run your projects efficiently with Scrum and Kanban - Li, Patrick (Professional expertise distilled., 2015)
If you want to get started with JIRA Agile and learn how to run your JIRA projects the agile way, then this is the perfect book for you. You will need to be familiar with the basics of JIRA, both from an end user's and an administrator's perspective. Experience with workflows, custom fields, and other administrative functions of JIRA will be useful.